2015
DOI: 10.1016/s2352-3018(15)00183-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of virological failure and major regimen change of initial combination antiretroviral therapy in the Latin America and the Caribbean: an observational cohort study

Abstract: Background Access to combination antiretroviral therapy (cART) is expanding in Latin America and the Caribbean (LAC). There is little information in this region regarding incidence of and factors associated with regimen failure and regimen change. Methods Antiretroviral-naïve adults starting cART from 2000-2014 at sites in seven countries throughout LAC were included. Cumulative incidence of virologic failure and major regimen change were estimated with death considered a competing event. Findings 14,027 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
4
19
1
Order By: Relevance
“…However, the rate of increase in CD4 counts was slightly faster in the groups with lower baseline CD4 counts. Our analyses revealed that it took approximately 6.5 years for the mean CD4 count trajectories to become indistinguishable based on overlapping the 95% confidence, which supports the recent global trend toward early ART initiation .…”
Section: Discussionsupporting
confidence: 70%
“…However, the rate of increase in CD4 counts was slightly faster in the groups with lower baseline CD4 counts. Our analyses revealed that it took approximately 6.5 years for the mean CD4 count trajectories to become indistinguishable based on overlapping the 95% confidence, which supports the recent global trend toward early ART initiation .…”
Section: Discussionsupporting
confidence: 70%
“…The threshold for classifying a measurement as undetectable was set at 400 copies/ml to account for changing detection limits of assays used at many of the sites over time. The second condition was added because it corresponds with clinical practices at some sites in the region 23. As VLs were not routinely performed at GHESKIO‐Haiti, all patients from this site were excluded from the virologic failure analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Virologic failure was defined as one of the following: (1) two consecutive HIV-1 RNA measurements above 50 copies/mL; (2) a single HIV-1 RNA measurement of above 1000 copies/mL [ 21 ].…”
Section: Methodsmentioning
confidence: 99%